The Concept of Developing the Square Area as a Public Space in Asahan Regency - Agung Pribadi; Abdi Sugiarto; Cut Nuraini (Yayasan Sinergi Multidimensi Kreatif, 2025)
This research aims to examine the Concept of Developing the Square Area as a Public Space in Asahan Regency.This study uses a qualitative approach to explore how the square area in Asahan Regency is developed as aneffective public space. The case study design will allow this research to focus on the square as a single case,exploring various aspects such as the role of the square in the social, economic, and cultural life of the community.This qualitative research uses several data collection techniques to obtain rich and in-depth information. Dataobtained from interviews, observations, and documents will be analyzed using thematic analysis methods. Theresults of the research of the Square function as a center for social, cultural, and recreational interaction, whichprovides space for the community to engage in activities and socialize. Although Asahan Regency Square alreadyhas supporting facilities, many challenges are faced, such as poor infrastructure conditions, lack of communityparticipation, and hygiene and security problems. The development of the square needs to be carried out throughvarious strategies, including infrastructure improvement, diversification of activities, community involvement,security and hygiene management, and cooperation with stakeholders. To ensure that the development of thesquare runs as expected, it is necessary to carry out periodic evaluation and monitoring. With the application ofthe right development concept, it is hoped that Asahan Regency Square can become a center of dynamic,environmentally friendly, and inclusive activities, which meet the needs of all groups of people.